2022
DOI: 10.1002/mrm.29469
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated 4D‐flow MRI with 3‐point encoding enabled by machine learning

Abstract: Purpose To investigate the acceleration of 4D‐flow MRI using a convolutional neural network (CNN) that produces three directional velocities from three flow encodings, without requiring a fourth reference scan measuring background phase. Methods A fully 3D CNN using a U‐net architecture was trained in a block‐wise fashion to take complex images from three flow encodings and to produce three real‐valued images for each velocity component. Using neurovascular 4D‐flow scans (n = 144), the CNN was trained to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Kim et al demonstrated a DL-based reconstruction for the 4D-Flow that produced three directional velocities from only three acquired flow encodings, without requiring the conventional fourth reference scan to measure the background phase [ 102 ]. They used the complex images from four velocity encodings (flow-compensated reference plus x, y, and z velocities) of 144 neurovascular patient datasets to train a 3D U-Net to predict the x, y, and z velocities.…”
Section: Application-specific Methodsmentioning
confidence: 99%
“…Kim et al demonstrated a DL-based reconstruction for the 4D-Flow that produced three directional velocities from only three acquired flow encodings, without requiring the conventional fourth reference scan to measure the background phase [ 102 ]. They used the complex images from four velocity encodings (flow-compensated reference plus x, y, and z velocities) of 144 neurovascular patient datasets to train a 3D U-Net to predict the x, y, and z velocities.…”
Section: Application-specific Methodsmentioning
confidence: 99%
“…39,115 Because CSF net flow rates are typically small, uncorrected phase offset errors may lead to false interpretation of the direction of CSF flow in compartments that are central to understanding normal and pathological CSF physiology (e.g., the CA 39 ). More recently, machine learning implementations have demonstrated the capability to remove background field offsets in neurovascular 4D flow MRI, 81 something that could be extended to 4D CSF flow.…”
Section: Low Velocities Associated With Csf Motionmentioning
confidence: 99%
“…78 Other studies have demonstrated the feasibility of accelerating neurovascular 4D flow acquisitions by 25% using machine learning and a convolutional neural network (CNN) that produces three directional velocities from three flow encodings, without requiring a fourth reference scan measuring background phase. 81 The authors used neurovascular 4D flow scans to train a CNN using supervised learning. The produced three-point velocities showed excellent agreement with the velocities derived from standard reconstruction using all four flow encodings with $1.5% errors in the velocity values, and correlations as high as 0.992.…”
Section: Current Approaches To Facilitate 4d Csf Flow Mrimentioning
confidence: 99%
See 2 more Smart Citations